Comparative analysis of seven types of phosphate transporters in forty species from the phylogenetic and transcriptomic perspective - Junyi Ren; Lulu Xie; Fu Li; Siyuan Zhang; Jianchang Gao; Bin Li (PLoS ONE, 2026)
Acquisition of phosphorus (P), an essential macronutrient for plants, is a limiting factor in most soils. Phosphate transporter proteins (PTs) play an indispensable role in inorganic phosphate (Pi) transport across the membrane barriers in plants. To understand the mechanisms associated with the P use efficiency of plants, we performed a comprehensive analysis of seven types of phosphate transporters—Pi-H + co-transporters [PHT1, PHT2, PHT3, and PHT4], plastid phosphate transporters (pPTs), glycerol-3-phosphate permeases (G3Pps), and SPX domain-containing PTs—across 40 species, from bacteria to higher plants. Using the amino acid sequences of PTs obtained by BLASTp, phylogenetic and structural analysis was performed. Analysis of conserved motifs within and between types of PTs was performed using the MEME program, and a pairwise genetic distance matrix was calculated in MEGA. Moreover, transcriptomic expression patterns in five tissues (root, stem, leaf, flower, and fruit) or in P starvation were examined in eight vegetable species using public databases. In total, 564 PHT1s, 94 PHT2s, 134 PHT3s, 228 PHT4s, 116 G3Pps, 546 pPTs, and 480 SPX-domain PTs were identified. The presence or copy number of different PT types varied among taxa, indicating that PHT3s, pPTs, and SPX-domain PTs are of eukaryotic origin, whereas PHT1s, PHT2s, PHT4s, and G3Pps are of prokaryotic origin. The absence of common motifs between the various PT types suggests that they originated and diversified independently. PHT1, G3Pp, and SPX-domain PT genes showed tissue-specific and P starvation induced expression, and thus are likely candidates for genetic modification strategies to obtain P-efficient crops.